2011
DOI: 10.4273/ijvss.3.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Hybrid Electrical Vehicle Structural Topology Optimisation Investigation Focusing on Crashworthiness

Abstract: As focus on the world climate rises, so does the demand for ever more environmentally friendly technologies. The response from the automotive industry includes vehicles whose primary propulsion systems are not based upon fossil fuels. On this basis a Low Carbon Vehicle Technology Project, partly funded by the European Regional Development Fund, is currently under way; part of this project involves designing a lightweight Body In White (BIW). This has been specifically tailored to suit the drive train and gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The topology optimisation study also included investigation of the optimal centre of mass (CM) locations with respect to key HEV components such as battery packs, feasibility and practicality of the CM locations, as well as vehicle dynamics. Further information on the topology optimisation study can be found in [10], [14] and [15]. The proposed vehicle structure in Fig.…”
Section: Topology Optimisation Resultsmentioning
confidence: 99%
“…The topology optimisation study also included investigation of the optimal centre of mass (CM) locations with respect to key HEV components such as battery packs, feasibility and practicality of the CM locations, as well as vehicle dynamics. Further information on the topology optimisation study can be found in [10], [14] and [15]. The proposed vehicle structure in Fig.…”
Section: Topology Optimisation Resultsmentioning
confidence: 99%
“…Within this load scenario, inertia relief is used to obtain the load equilibrium of the model [18]. Thus, the applied loads F and M are balanced by inertial accelerations that automatically provide forces distributed over the body in such a way that the sum of the applied forces is equal to zero.…”
Section: Front Wheel Brakementioning
confidence: 99%
“…Creating loadcases representative of the crash scenarios and the maximum crash pulse obtained from the FE (crashworthiness) analyses of section 2, the topology optimisation could be completed. This utilised an isotropic material model and the Inertia Relief (IR) boundary conditions [7], [8], [9], [10] and [11] it was possible to extract suggestions for idealised loadpaths of the future Microcab vehicle as illustrated in Figure 25. From the optimisation results, Figure 25, it may be suggested that the front-end of the current Microcab concept design does not require any significant modifications.…”
Section: Future Topologymentioning
confidence: 99%